S100A8 expression in oviduct mucosal epithelial cells is regulated by estrogen and affects mucosal immune homeostasis. - Xiaodan Li (Public Library of Science (PLoS), 2021)
Chronic inflammation can cause oviduct mucosal damage and immune dysfunction, leading to infertility, early pregnancy loss, ectopic pregnancy, tumors, and a decrease in reproductive capacities in female animals. Estrogen can suppress immune responses in different tissues and oviducts, and regulate the oviduct immune balance; however, the underlying mechanisms remain unclear. The objective of this study was to explore the mechanism of estrogen-regulated oviduct mucosal immunity and discover new estrogen targets for regulating oviduct mucosal immune homeostasis. Sheep oviduct epithelial cells (SOECs) were treated with 17-β estradiol (E2). Transcriptome sequencing and analysis showed differentially expressed S100 calcium-binding protein A (S100A) genes that may participate in the oviduct mucosa immunoregulation of estrogen. Quantitative polymerase chain reaction and immunocytochemistry analysis showed that S100A8 expression changed dynamically in E2-treated SOECs and peaked after 7 h of treatment. Estrogen nuclear receptors and G protein-coupled membrane receptors promoted E2-dependent S100A8 upregulation. The S100A8 gene was disrupted using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 method. Levels of inflammatory factors interleukin (IL)-1β and IL-4 were significantly upregulated in S100A8-knockdown SOECs, whereas those of the anti-inflammatory factor IL-10 was downregulated. Following S100A8 knockdown in SOECs treated with E2 for 7 h, IL-10 levels increased significantly. Estrogen affected oviduct mucosa immune function and dynamically regulated S100A8 in SOECs. S100A8 knockdown caused an excessive immune response, indicating that S100A8 is beneficial for maintaining immune homeostasis in the oviduct mucosa. Moreover, estrogen can compensate for the effect of S100A8 knockdown by upregulating IL-10.